Case Report: Lithoplasty-Assisted Trans-Axillary Transcatheter Aortic Valve-in-Valve Implantation - Cerillo, Alfredo Giuseppe; Pennesi, Matteo; Iannone, Luisa; Giustini, Giorgia; de Cillis, Paolo; Valenti, Renato; Marchionni, Niccolò; Stefano, Pierluigi (Frontiers in Cardiovascular Medicine, 2021)
We present the case of a severely symptomatic patient with a malfunctioning aortic bioprosthesis and severe multidistrict atherosclerosis that was addressed to our unit for transcatheter valve-in-valve implantation. The imaging and clinical assessment that led to the selection of the access route is discussed.